El caso Banchero, of Guillermo Thorndike: Printed source that explains the cult to Luis Banchero Rossi, secular saint, in Lima - Hernández Lefranc, Harold (2020)
The existence of the cult to Luis Banchero Rossi —Peruvian businessman of the fish industry, who was murdered in 1972—, in the Angel cemetery, it demands the interest for its genesis, being that it is a religious cult to a secular character. The present text find that this is possible for two reasons: the violent death produce holiness; and the sacralization is not restricted to the limits of the institutionalized religion. Moreover, it proposes that, in the efficient, a factor that explains the cult is the book El caso Banchero (1973), of the journalist and writer Guillermo Thorndike. Furthermore, it practices an anthropological exegesis of it; and it evidences in this, mystified and messianic traits of the character, his life and his death; and they are understood like antecedents of the cult. Popular cults are disseminated fundamentally through of the orality, not by the written word; nevertheless, in this case the limits between the popular culture and the written text become blurred, which intermediary is the press.